2007
DOI: 10.1177/030802260707000105
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Older People to Stay at Home: How Adaptable are Existing Properties?

Abstract: A multiprofessional research project examined in detail the factors that affect the adaptability of existing housing and explored issues relating to the introduction of assistive technology into the existing homes of older people in order to provide them with the opportunity to ‘stay put’. The research reported here investigated the feasibility of adapting the existing stock of social housing and the resulting costs and outcomes of introducing assistive technology. This paper outlines that part of the project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…They looked at existing homes and made recommendations for various adaptations which could increase the safety of the senior adults thereby allowing them to stay in their homes [21]. Based on individual needs, some of their recommendations include using lever door handles, installing amplifiers on door bells and telephones, installing grab rails and handrails in appropriate locations, ramps, stair lifts, external lighting with passive infra-red, lowered light switches, raised electrical outlets, level thresholds, wider doors and corridors, and electric window and door openers.…”
Section: 9mentioning
confidence: 99%
“…They looked at existing homes and made recommendations for various adaptations which could increase the safety of the senior adults thereby allowing them to stay in their homes [21]. Based on individual needs, some of their recommendations include using lever door handles, installing amplifiers on door bells and telephones, installing grab rails and handrails in appropriate locations, ramps, stair lifts, external lighting with passive infra-red, lowered light switches, raised electrical outlets, level thresholds, wider doors and corridors, and electric window and door openers.…”
Section: 9mentioning
confidence: 99%
“…For the augmented packages, the corresponding figures are break-even periods of 1-7 years, and typically about half the average life expectancy. However, these are average figures across all property types and, as discussed in Goodacre et al (2007) and Lansley et al (2004), the cost of adapting properties varies greatly. For those properties where adaptation is not straightforward, these costs can be so high as to eliminate any potential saving, but for easy-to-adapt properties the costs can be surprisingly low, even where the needs of the user are complex and extensive, leading to very significant savings.…”
Section: Cost Trajectories: Savings and Shortfalls Over Time And In Rmentioning
confidence: 99%
“…The challenges created in respect of housing have, until recently, received less attention, but over the past decade there has been a new recognition of its importance. Goodacre et al (2007) reported on research that examined the feasibility of adapting the existing stock of social housing and installing assistive technology (AT), in order to facilitate 'ageing in place'. It showed how the costs varied between and within different types of property, and identified those factors that result in a property being easy and inexpensive to adapt and those that make adaptation difficult or costly, or even impossible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational therapists have also used other procedures, including checklists and home visit reports, and have implemented valuable accessibility evaluation tools relating physical abilities, taking into consideration characteristics of the built environment such as the Housing Enabler (Iwarsson, 1999;Goodacre et al, 2007). These are useful tools to measure the relationship between the capacities of individuals and the demands of the environment (Zemcke and Clarck, 1996).…”
Section: Introductionmentioning
confidence: 99%